Reduced Opioid Consumption with Pericapsular Nerve Group Block for Hip Surgery: A Randomized, Double-Blind, Placebo-Controlled Trial - Chan Jong Chung; Deuk Won Eom; Tae Young Lee; Sang Yoong Park (Pain Research and Management)
The pericapsular nerve group (PENG) block targets the nerves innervating the anterior hip surface; however, few studies on this technique are currently available. We investigated the effects of the PENG block on postoperative opioid consumption after a hip surgery. This was a randomized, double-blind, placebo-controlled study conducted at a single institution. Fifty patients undergoing hip surgery were randomly allocated, 25 in each group, to receive a PENG block either using 25 mL of 0.5% ropivacaine (PENG group) or 25 mL of saline (control group). The primary outcome was the total opioid consumption 24 h postoperatively. The secondary outcomes were postoperative pain scores, time to first opioid demand, sensory block efficiency, quadriceps muscle strength, complications, and patient satisfaction. Compared with those in the control group, patients in the PENG group had a significantly lower total opioid consumption 24 h postoperatively (440.72 ± 242.20 μg vs. 611.07 ± 313.89 μg, P = 0.037) and significantly lower pain scores at 30 min postblock and 6 postoperatively (P<0.001 and P<0.001, respectively). The time to first opioid demand was significantly shorter in the control group than in the PENG group P<0.001. Sensory block effectiveness was better in the PENG group 30 min postblock and 6 and 12 h postoperatively than in the control group. Patient satisfaction was also better in the PENG group than in the control group. There were no differences in the other outcomes. The PENG block reduced the total opioid consumption in the first 24 h after hip surgery with no significant effects on quadriceps muscle strength and complication rate. This study was registered at the Korea Clinical Research Information Service (cris.nih.go.kr; Reg. No. KCT0006348) on July 16, 2021.